Performance of utility scale PV Plant in Malaysia and India: a comparative study - Sudhakar, K.; Mahendran, Samykano; Ria, - (Institute of Electrical and Electronics Engineers Inc., 2018)
In this research work, we have compared the capabilities and outputs of a 8MW solar mono-Si and poly-Si PV systems for the cities of Kuala Lumpur and Lucknow. The simulation is done with the help of PVsyst software with uniform parameters used for all the simulations. Individual losses for all the cases have been quantified and it can be seen that the losses due to temperature constitutes for the majority of it. This study helps us understand the effect of temperature variation, the sun's position in reference to the earth's horizon and also the effect of using mono-Si versus using poly-Si systems.